2004
DOI: 10.1159/000076765
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Capsaicin Treatment Affects Rat Thymocyte Proliferation and Cell Death by Modulating Substance P and Neurokinin-1 Receptor Expression

Abstract: Herein we provide evidence that substance P (SP) and its neurokinin-1 receptor (NK-1R) expressed on thymocytes counteract thymus depletion induced by neonatal capsaicin (CPS) treatment by affecting thymocyte proliferation and apoptotic death. SP administration reversed the CPS-mediated inhibitory effects on the total thymocyte number and subset distribution, namely CD4+ and CD4– CD8– cells, through its interaction with NK-1R as shown by concomitant NK-1R (SR140333) antagonist administration. SP-induced enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We have previously reported that neonatal CPS treatment induces apoptosis of rat thymocytes, 4,6 but evidence on the vanilloid receptor(s) mediating these functional effects are still missing. Thus, in order to directly demonstrate VR1 mRNA expression on rat thymocytes, we initially performed real-time quantitative PCR analysis on Ficoll gradient-purified (499%)…”
Section: Expression Of Vr1 On Rat Thymocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that neonatal CPS treatment induces apoptosis of rat thymocytes, 4,6 but evidence on the vanilloid receptor(s) mediating these functional effects are still missing. Thus, in order to directly demonstrate VR1 mRNA expression on rat thymocytes, we initially performed real-time quantitative PCR analysis on Ficoll gradient-purified (499%)…”
Section: Expression Of Vr1 On Rat Thymocytesmentioning
confidence: 99%
“…47 We have previously reported that neonatal CPS treatment in the rats results in a marked reduction of thymus weight and cellularity that is associated with decreased thymocyte proliferation in response to T-cell mitogens and induction of apoptotic cell death. 6 However, the molecular mechanisms underlying the proapoptotic effects of CPS on rat thymus are presently unknown.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypoth- esized that sc9758 cross-reacted with epithelium-related substances produced by the death process. Actually, SP seems to induce cell death by way of the NK-1 receptor (Castro-Obregón et al 2002;Santoni et al 2004;Meshki et al 2009; see also Introduction). We identified NK-1 receptor in most of the sc9758-positive sites.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptide substance P (SP) and its receptor, neurokinin-1 receptor, were first identified by an in vitro study using cultures of rat embryonic nerve cells, and mediate an alternative, non-apoptotic form of programmed cell death (Castro-Obregón et al 2002). SP has killing activity against proliferating non-neuronal cells (Meshki et al 2009;D'Souza et al 2007;Santoni et al 2004). This type of cell death requires gene expression, displays non-apoptotic morphology, and is independent of caspase activation.…”
Section: Introductionmentioning
confidence: 99%